Coating and Hardening of Plastic Recycling Machine Blades Using Flux–Cored Arc Welding (FCAW) Process - Murad Ayad Debeski; Maryam Mohamed Morghem; Khaled Suliman Elgomati (African Journal of Advanced Pure and Applied Sciences, 2025)
Plastic pollution presents a critical global challenge, largely driven by inadequate waste management and recycling initiatives. Plastic shredders play a pivotal role in addressing this issue by fragmenting plastic waste into manageable pieces for reuse. This study focuses on enhancing the mechanical characteristics of low-carbon steel blades used in plastic shredders through utilizing wire welding techniques. Specifically, the research examines the microstructural and microhardness properties of low-carbon steel blades enhanced through an arc with a flux core arc E71T-GS filler electrodes, a single buttering layer of hard-facing material is applied to improve wear resistance and durability. Metallurgical analysis, using optical microscopy and micro-Vickers hardness testing, revealed the presence of martensitic and tempered needle-like structures in the heat-affected zone. These features are influenced by specific current and voltage parameters during welding. Comparative analysis was conducted with blades sourced from two other companies (denoted as M and U) to establish performance benchmarks. The hard-facing layer, enriched with (Fe,Cr)₇C₃ carbides embedded in a martensite-austenite matrix, demonstrated significantly enhanced hardness and wear resistance. Vickers hardness testing confirmed superior microhardness in the hard-facing layer, with a gradual and cohesive transition to the softer steel substrate. This optimized microstructure allows the blades to endure high-stress conditions while maintaining durability and toughness. These findings underscore the potential of molten wire welding to significantly enhance the performance and lifespan of shredder blades, providing valuable insights for the design of more efficient plastic waste management systems.